The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5005/jp-journals-10005-1197
|View full text |Cite
|
Sign up to set email alerts
|

To Evaluate the Effect of Different Adhesive Materials on the Microleakage of Bonded Amalgam Restorations: An in vitro Study

Abstract: This study evaluated the ability of different adhesive materials in reducing the microleakage in class V amalgam restorations. Standardized class V cavities were prepared on the facial surface of 56 noncarious human premolars, they were then randomly divided into control and experimental groups based on adhesives used. Group I was the control group with copal varnish, group II had Panavia F 2.0, group III contained Vitrebond Plus and group IV had RelyX ARC as adhesives. Amalgam was hand condensed into each pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Adhesive systems have been developed (and continue to be developed) in order to eliminate the microleakage that has caused problems for both the traditional amalgam and other restorations (17)(18)(19)(20)(21)(22)(23). Adhesives are commonly used in dentistry today.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive systems have been developed (and continue to be developed) in order to eliminate the microleakage that has caused problems for both the traditional amalgam and other restorations (17)(18)(19)(20)(21)(22)(23). Adhesives are commonly used in dentistry today.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with Ghavamnasiri recent study and different examiners have likewise be demonstrated it to diminish the decrease micro-leakage and post-operative sensitivity. 17 Since cavity varnish is utilized as a part of very thin film, therefore, they are not utilized as coating material. Zinc phosphate can reasoning postoperative sensitivity due to having low pH.…”
Section: Discussionmentioning
confidence: 99%